Assessing Personal and Social Competencies among Successful Entre-preneurs - Othman, Abdul Kadir; Noranee, Shereen; Munap, Rudzi; Malik, Ikmal bin Abd (International Business and Accounting Research Journal, 2024)
Entrepreneurship success has become a deep concern among government agencies, non-governmental organizations, and other related bodies, especially after the COVID-19 pandemic. The companies that were greatly affected during the pandemic were small and medium enterprises. These firms are considered fragile to drastic changes since they have limited resources to adapt to the changing business environment. Among the factors that affect the firm’s performance is entrepreneur competencies. The current study is undertaken to investigate the influence of entrepreneur competencies comprising social and personal competencies on firm performance. 152 responses were collected via social media platforms from SME entrepreneurs and analyzed using factor analysis and multiple regression analysis. The findings indicate that only strategic planning and flexibility significantly predict SME firm performance. Entrepreneurs must be equipped with these required competencies to set the correct direction for their firms, allocate sufficient resources, and be flexible to adjust the existing strategic plans to improve their performance.